Letter (copy) : Interned anti-Fascists in North Africa - Citrine, Walter, 1887-1983
035-0091-001 International. WMC/EAB/DT/673. 25th March, 1943. Mr. W. Schevenels, International Federation of Trade Unions, Transport House, Smith Square, S.W.1. Dear Mr. Schevenels, INTERNED ANTI-FASCISTS IN NORTH AFRICA. Your note dated 16th March regarding the release of interned Anti-Fascists in North Africa was considered by the International Committee at their meeting this week. The Committee felt that further information was required before they could consider approaching the Government on this question. I shall be glad, therefore, if you could let me have any information which is in your possession regarding this matter, particularly in view of the report which was carried in the New York Press last week to the effect that some 750 Anti-Fascists had recently been released. It would also be useful to know whether our Spanish comrades have made any direct appeal to either the British Foreign Office or the Fighting French and, if so, with what effect. Yours sincerely, General Secretary. 292/946/35/91